Efektifitas Edukasi Rokok Elektrik dalam Menurunkan Kejadian Kanker Paru pada Kelompok Remaja - Aminah, Ai; Allenidekania, Allenidekania; Maria, Riri (Journal of Telenursing (JOTING), 2024)
This research aims to evaluate the success of quitting smoking in adolescents through education provided in several countries regarding electronic cigarettes/VAPE. The method used is a systematic review with the PRISMA search strategy. Initial selection involved Sage Journals, Clinical Key, Scopus, and Proquest. The results of the research show that the ten journals in the review show high concern about smoking among school students, education increases knowledge about the dangers of smoking, although the desire to smoke still exists, education via social media according to the style of teenagers is more effective, there is still an opinion that VAPE is not dangerous such as tobacco cigarettes, and there is an effective signal for diversion methods to stop smoking such as yoga, as well as the importance of attention to teenagers, consistent evaluation and application of discipline in schools for not smoking, because it is found that teenagers imitate their parents, teachers and the school environment in terms of smoking. . The conclusion is that there is a need for consistency from health actors, government, education services and health institutions who are concerned about adolescent health to develop smoking cessation programs, the importance of strict laws and consistent evaluation of the interventions carried out. Keywords: Education, Teenagers, E-Cigarettes, Lung Cancer